Social lives and afterlives of a malaria vaccine trial: partnerships in practice - Genus, Sandalia (The University of Edinburgh, 2018)
This thesis focuses on the development of a malaria vaccine as an avenue to explore global health partnerships. In the last twenty years, public-private partnerships have become a prominent organizational form in global health. Hundreds of large transnational collaborations and countless smaller collaborations between the public, private and non-profit sectors have been established. Partnerships have been supported by the large increase of donor funding for research and control of infectious diseases in impoverished countries and many aim to develop or provide vaccines, medicines or interventions. Analysts generally agree that partnerships are saving many lives and revolutionizing drug and vaccine development for infectious diseases. However, while partnership is a notion that connotes equity and mutuality, often global health partnerships operate in contexts that involve vast disparities in power and resources and there is little known about the impacts of partnerships on the places where they operate. This raises the questions: How do global health partnerships operate in practice? What are their impacts in the places where they operate? Addressing these questions, this thesis examines a partnership established to develop the most advanced malaria vaccine, named RTS,S. Based on 17 months of ethnographic research in Tanzania and interviews with representatives of partnering organizations in Belgium and the United States, I trace the development of the RTS,S vaccine from laboratories to its clinical trials across Africa. I explore the social relationships formed between private companies, philanthropic institutions and non-profit organizations in the North, and research institutions and communities in north-eastern Tanzania, where a malaria vaccine clinical trial was conducted. Analyzing the impacts of the malaria vaccine partnership, I focus on community development, construction of infrastructure, the building of human capacity, provision of health care and extraction of data. The focus on partnerships is intended to improve understanding about this ever-increasing social, political and economic formation in global health, and contributes to discussions and debates about how partnerships operate and their role in international development, global health governance and transnational medical research.
Keywords: global health; development; partnership; technology; anthropology; ethnography; Tanzania